Particulate matter exposure in roadwork companies: A mental models study on work safety. (December 2019) - Stege, T.A.M.; Bolte, J.F.B.; Claassen, L.; Timmermans, D.R.M.
Highlights: Employees have superficial knowledge about particulate matter (PM). Employees know about prevention methods, but do not always protect themselves. Periodical work safety meetings can be useful, but are often too ritualistic. Risk communication should focus on core subjects and mental model discrepancies. A good safety culture empowers workers to start a dialogue on PM risk. Abstract: Particulate matter (PM) exposure, amongst others caused by emissions and industrial processes, is an important source of respiratory and cardiovascular diseases. There are situations in which blue-collar workers in roadwork companies are at risk. This study investigated perceptions of risk and mitigation of employees in roadwork (construction and maintenance) companies concerning PM, as well as their views on methods to empower safety behavior, by means of a mental models approach. We held semi-structured interviews with twenty-two employees (three safety specialists, seven site managers and twelve blue-collar workers) in three different roadwork companies. We found that most workers are aware of the existence of PM and reduction methods, but that their knowledge about PM itself appears to be fragmented and incomplete. Moreover, road workers do not protect themselves consistently against PM. To improve safety instructions, we recommend focusing on health effects, reduction methods and the rationale behind them, and keeping workers' mental models into account. We also recommend a healthy dialogue about work-related risk within the company hierarchy, to alleviate both information-related and motivation-related safety issues.